REKONSTRUKSI DELIK ADUAN PERZINAAN DALAM KUHP NASIONAL: RASIONALITAS YURIDIS KETAHANAN KELUARGA DAN PERAN SIRI' NA PESSE DI PAREPARE - Oktaviani; Mutmainna; Muhammad Fadil Widhana; Nurfajri Hasbulllah; Khaerunnisa (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The expansion of adultery legal standing to parents and children under Article 411 of Law No. 1/2023 triggers an academic 'engineering paradox.' Employing a normative-empirical legal method with a socio-legal approach, this study analyzes the juridical rationality of this expansion and its impacts on family resilience in Parepare City. Data were gathered through purposive sampling, combining documentary analysis of 24 police case files (2020–2024) and semi-structured deep interviews with five key informants. The dataset was analyzed using an interactive qualitative model integrated with thematic analysis, and its rigor was validated through member-checking and theoretical triangulation. The ultimate novelty of this research is offering the 'cultural filter mechanism' concept as a theoretical model to moderate complaint-based offenses within a living law framework. Empirically, thematic analysis reveals that the Siri’ na Pesse system moderates state law; while Siri’ triggers honor defense, Pacce (empathy) acts as a social brake, channeling conflicts into Tudang Sipulung (customary council) rather than formal courts. This research contributes theoretically to constructing a 'Restorative-Cultural Enforcement Model' that harmonizes national restorative regulations (Perpol, Perja, and PERMA) with indigenous institutions. It positions traditional mediation as a crucial institutional shield to preserve family resilience from the destructive nature of modern criminal proceedings.